2016
DOI: 10.1080/2162402x.2016.1160181
|View full text |Cite
|
Sign up to set email alerts
|

miRNA dynamics in tumor-infiltrating myeloid cells modulating tumor progression in pancreatic cancer

Abstract: Myeloid cells including tumor-associated macrophages (TAM) and myeloid-derived suppressor cells (MDSC) are known as important mediators of tumor progression in solid tumors such as pancreatic cancer. Infiltrating myeloid cells have been identified not only in invasive tumors, but also in early pre-invasive pancreatic intraepithelial precursor lesions (PanIN). The functional dynamics of myeloid cells during carcinogenesis is largely unknown. We aimed to systematically elucidate phenotypic and transcriptional ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…During the development of schistosomiasis, significant up-regulation of miR-146a/b was reported in macrophages, which promoted the polarization of IFN-g-induced macrophages into M1 by targeting signal transducer and activator of transcription 1 (44). miR-21-5p and miR-21-3p altered the expression of chemokine (C-X-C motif) ligand 10 (CXCL-10) and chemokine (C-C motif) ligand 3 (CCL-3), respectively, which led to macrophage polarization to M1 (45). miR-21 also prevented macrophages from polarizing to M2 by interfering with prostaglandin E 2 production (46); however, the mechanism that underlies the regulation of miR-21 remains unclear.…”
Section: Discussionmentioning
confidence: 98%
“…During the development of schistosomiasis, significant up-regulation of miR-146a/b was reported in macrophages, which promoted the polarization of IFN-g-induced macrophages into M1 by targeting signal transducer and activator of transcription 1 (44). miR-21-5p and miR-21-3p altered the expression of chemokine (C-X-C motif) ligand 10 (CXCL-10) and chemokine (C-C motif) ligand 3 (CCL-3), respectively, which led to macrophage polarization to M1 (45). miR-21 also prevented macrophages from polarizing to M2 by interfering with prostaglandin E 2 production (46); however, the mechanism that underlies the regulation of miR-21 remains unclear.…”
Section: Discussionmentioning
confidence: 98%
“…Currently, an increasing number of reports have demonstrated the association between miRNA and tumor metastasis, which is regulated by miRNA mediating a number of signal pathways ( 40 , 41 ). Liu et al ( 42 ) indicated that miR-153 could enhance the therapeutic effects of gemcitabine, by targeting SNAI1 in pancreatic cancer and gastric carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNA dysregulation widely occurred in NSCLC, which might contribute to tumor occurrence and progression (16). To verify whether curcumin could regulate the expression of miR-206 in A549 cells, we treated the A549 cells with 10 and 20 μmol L -1 curcumin for 24 h. Then the relative expression of miR-206 was detected by real-time RT-PCR.…”
Section: Mir-206 Is Upregulated In Curcumin-treated A549 Cellsmentioning
confidence: 99%